Dietary polymer-coated urea enhances the goats lactational performance, excretion of microbial purine derivatives and blood metabolites in the semi-arid zone of Iran - Mitra Mazinani; Abbas Ali Naserian; Mohsen Danesh Mesgaran; Reza Valizadeh; Abdelfattah Z. M. Salem (Acta Scientiarum. Animal Sciences, 2022)
This study aimed to determine the effect of using different sources of nitrogen to supply part of degradable intake protein needs in lactating goat performance and its effect on excretion of microbial purine derivatives and blood metabolites. Thirty-two lactating Saanen goats (body weight 38.85 ± 2.14 kg and 1979 ± 0.25 g day-1 milk yield) were used in a one-way ANOVA completely randomized design. Goats were assigned to the following treatments for a 10-wk experimental period: 1) Control (canola meal as a nitrogen source); 2) Urea (0.5% urea); 3) Optigen (0.55% Optigen- Alltech. Inc., Lexington, KY) and 4) Polymer-Coated Urea (PCU- international patent number: A01K5/00, 0.7% PCU) based on dry mater intake. Non-protein nitrogen groups had a comparative effect (p > 0.05) between control and other treatments on milk composition, microbial protein synthesis and they affected on blood factors including urea, cholesterol, and ALT. Dry matter intake decreased (p > 0.05) in PCU, Optigen, Urea than Control goats. Synthesis of microbial protein in PCU goats was 22.5 g day-1 and it was greater (p > 0.05) than other treatments. Plasma cholesterol was increased in PCU and Optigen, whereas urea concentration was increased in Urea and Control goats. Milk production was higher in PCU than Urea and Control. Feed conversion ratio was improved (p > 0.05) in PCU and Optigen goats versus other treatments. This study demonstrated that polymer-coated urea can be utilized as a nitrogen source and improve goats milk performance.